Situation and recent evolution of heritage tourism in China: a bibliometric analysis - Shen, Shuwen; Troitiño Torralba, Libertad (Anales de Geografía de la Universidad Complutense, 2026)
This study examines the evolution of research on heritage tourism in China from 1999 to 2023 through a bibliometric approach. By integrating data from CNKI and Scopus, it analyzes publication trends, thematic structures, and knowledge network configurations. The findings reveal a progressive trajectory from an initial phase characterized by dispersed structures to the formation of consolidated thematic clusters, and subsequently to a more integrated and complex configuration. In the early stage, research primarily focused on the relationship between heritage conservation and tourism development. During the second phase, themes such as sustainability, stakeholders, and destination image gained prominence. In recent years, the field has further expanded to incorporate issues related to digitalization, urban governance, and cultural identity. A cross-database comparison highlights structural differences: domestic publications tend to concentrate on specific heritage types and regional practices, whereas internationally published research is more strongly embedded in global theoretical frameworks. Overall, the study provides a structural perspective on the logic of knowledge production in China’s heritage tourism research and offers an empirical foundation for future comparative and theoretical investigations.
Keywords: heritage tourism; cultural heritage; systematic bibliographic network analysis; chinese context